Effect of Zataria multiflora Boiss. essential oil on probability of growth initiation of Salmonella typhimurium in a brain heart infusion broth - AA Basti; V Razavilar; A Misaghi; R Abbasifar; B Radmehr; F Khalighi Sigaroodi (Institue of Medicinal Plants, ACECR, 2004)
The growing interest in the substitution of chemical food preservatives, both antimicrobials and antioxidants, by natural ones has fostered research on the vegetable source and screening of plant extracts and essential oils in order to identify acceptable natural alternatives. In this study, log probability percentage (Log P%) of growth of Salmonella typhimurium in Brain Heart Infusion (BHI) broth as affected by different concentrations of Zataria multiflora Boiss essential oil (0.0, 0.03 and 0.06%) during 21 days storage at three temperatures (35, 25 and 15ºC) was investigated. The Log P% of S. typhimurium was affected significantly (P < 0.05) by different concentrations of the essential oil. The Log P% of S. typhimurium in BHI broth with 0% essential oil at 35, 25 and 15ºC were 1.07, 1.07 and 0.41 respectively. While in BHI broth with 0.03 and 0.06% essential oils were -2.93, -3.24 and -4.23 and -4.23, -4.23 and -4.23 respectively. According to the results, the Log P% of growth of S.typhimurium was decreased by increasing of the concentration of essential oil.